HYDRAULIC DESIGN AND STABILITY ANALYSIS OF CILIWUNG RIVERCIPINANG RIVER FLOODWAY - Juanda, Wilbert
Flood disasters seems to have been a common thing that happen in Jakarta when heavy rain occurs. The area that almost experience flooding is Ciliwung River at East Jakarta. River normalization has been carried out but it is not sufficient to accommodate the overflowing river water due to heavy rains. In overcoming the problem of flooding, a floodway system is planned to drain excess water that cannot be accommodated by the Ciliwung River to the East Canal Flood (BKT) through the Cipinang River which is 1.3 kilometers away. The focus in this Final Assignment is to design inlet weir, tunnels and outlet weir in order to drain the planned discharge of 60 m3/s which is the maximum capacity that can be accommodated by the East Canal Flood (BKT). Initial studies of hydrological analysis of the Ciliwung River and Cipinang River were needed to obtain the magnitude of the flood discharge plan of both rivers. The discharge flood plan will be used to observe the high water level during the flooding of both rivers. The water level of these two rivers will be the basis in designing the dimensions of water buildings to drain the discharge plan. Hydraulic design of water buildings based on 5 years flood discharge. The design output are 5.4 metres inlet weir measured from the bottom of the Ciliwung River, 2.7 metres outlet weir measured from the bottom of the Cipinang River and 2 pieces tunnels with a diameter of 3.5 metres to drain the planned discharge. Stability analysis of the design has been conducted showing that the structure is safe against possible sliding and overturning.